The influence of product quality, brand image, and electronic word of mouth on purchase decisions of Glad2Glow products on tiktok shop in Batam city - Jesvabbyona Jesvabbyona; Alice Erni Husein (International Journal of Applied Finance and Business Studies, 2026)
This study examines the influence of Product Quality, Brand Image, and Electronic Word of Mouth (E-WOM) on consumers’ Purchase Decisions regarding Glad2Glow products on TikTok Shop in Batam City. A quantitative approach was employed using a survey method, with data collected from 100 respondents selected through purposive sampling. Primary data were obtained through questionnaires measured using a five-point Likert scale and analyzed using multiple linear regression with SPSS 26. The results indicate that Product Quality, Brand Image, and E-WOM each have a positive and significant effect on Purchase Decisions. Product Quality significantly enhances consumer confidence through product durability, material quality, conformity with product descriptions, and performance. Brand Image positively affects purchasing behavior by strengthening consumer trust and perceptions of brand superiority and uniqueness. E-WOM exerts the strongest influence, demonstrating the importance of online reviews, recommendations, and digital interactions in shaping consumer decisions. Simultaneous testing confirms that Product Quality, Brand Image, and E-WOM collectively have a significant effect on Purchase Decisions. The coefficient of determination shows that these variables explain 89.3% of the variance in Purchase Decisions, while 10.7% is explained by other factors not included in the model. The findings highlight the importance of maintaining product quality, strengthening brand image, and optimizing positive E-WOM strategies to improve consumer purchasing decisions in digital marketplace environments.